Implementation of the UN Convention on the Rights of Persons with Disabilities: A Comparison of Four European Countries with Regards to Assistive Technologies - Tanja Bratan; Piret Fischer; Maria Maia; Vera Aschmann (Societies, 2020)
The United Nations Convention on the Rights of Persons with Disabilities (CRPD) is an international treaty that aims to promote, protect and ensure the rights of persons with disabilities so that they can fully participate in society and enjoy the same freedoms and opportunities as others. It provides an important framework for the inclusion of persons with disabilities with the help of Assistive Technologies (AT). This paper assesses and compares the implementation of the CRPD with regards to the availability of AT in four countries (Germany, Hungary, Portugal and Sweden), which to some extent represent different European regions. The paper is based on a review of relevant academic literature, the DOTCOM database and regulatory documents as well as on five validation interviews with national experts. In the countries studied, anti-discriminatory and other legislation is included at the highest level of the legal framework and contains detailed rules on definitions, remedies and legal procedures. There are specific prohibitions in several fields, such as employment, housing, and healthcare. Nonetheless, there are still cases of non-compliance with the CRPD and of laws and regulations which discriminate against persons with a disability. Additionally, there are great variations between countries. As very positive examples of favourable regulatory frameworks for furthering inclusion with the help of ATs do exist, there may be benefit in raising awareness of such examples to support other countries in developing their own measures.